2017
DOI: 10.3390/socsci6040126
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Definition of Technology from an Ethological Perspective

Abstract: Definitions, uses, and understanding of technology have varied tremendously since Jacob Bigelow's Elements of Technology in 1829. In addition to providing a frame of reference for understanding technology, the purpose of this study was to define or describe it conceptually. A determination of dimensions comprising technology was made by critiquing historical and contemporary examples of definition by Bigelow and Volti. An analytic-synthetic method was employed to deconstruct both definitions spanning two centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 19 publications
1
31
0
6
Order By: Relevance
“…The third is the philosophical concept, where Verkerk et al (2015), identified three core areas of philosophy function in technology which are the technology analytical function (function upon which technology can be studied and evaluated), critical technology function (a query on its usefulness), and the directional technology function (what is the future of technology development). Carroll (2017), corroborated the above view of philosophy in technology positing a three-core concern dealing essentially with the purpose, function and benefit of technology to man. The fourth concept area is the entrepreneurial (business) concept, wherein technology is seen as business for profit through the offering of goods (products) and services.…”
Section: An Adaptive Approach To the Concepts Of Technology And Human Societysupporting
confidence: 68%
“…The third is the philosophical concept, where Verkerk et al (2015), identified three core areas of philosophy function in technology which are the technology analytical function (function upon which technology can be studied and evaluated), critical technology function (a query on its usefulness), and the directional technology function (what is the future of technology development). Carroll (2017), corroborated the above view of philosophy in technology positing a three-core concern dealing essentially with the purpose, function and benefit of technology to man. The fourth concept area is the entrepreneurial (business) concept, wherein technology is seen as business for profit through the offering of goods (products) and services.…”
Section: An Adaptive Approach To the Concepts Of Technology And Human Societysupporting
confidence: 68%
“…Volti (2009, p. 6) defines technology as "a system created by humans that uses knowledge and organization to produce objects and techniques for attaining specific goals". Technology, in this view, shows the ability to perform specific function, purpose and contribute to attaining a well-defined goal (Carroll, 2017), and comprehends information technology (Turban, 2008), digital technology (Giones & Brem, 2017), green technology (Chen, Luo, Sato, Wakatsuki, & Masunaga, 2009;Chen, 2013), and other kinds of technology that are linked to business needs (Phaal, Farrukh, & Probert, 2001). In fact, the core characteristic of technology is its applicability to problem-solving.…”
Section: Technology: Concept and Relevancementioning
confidence: 99%
“…Here Human Enhancement can be seen as a matter of control over natural processes or conditions, which are experienced as undesirable and flawed [ 19 ]. The means by which this control over nature is commonly exercised is technology [ 7 , 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…But what is technology? Carroll [ 22 ] carried out a careful and comprehensive ethological analysis of the timeless essence of technology. She argued that any technology consists of three core aspects: the possession or ascription of a function (I.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation